Longitudinal assessment of SARS-CoV-2 IgG seroconversionamong front-line healthcare workers during the first wave of the Covid-19 pandemic at a tertiary-care hospital in Chile - IRURETAGOYENA BRUCE, MIRENTXU INES; Macarena R. Vial; Maria Spencer-Sandino; Pablo Gaete; Anne Peters; DELGADO BECERRA, OROZIMBA IRIS; Inia Perez; Claudia Calderon; PORTE TORRE, LORENA ISABEL; Alicia Anderson; MUNITA SEPULVEDA, JOSE MANUEL; LEGARRAGA RADDATZ, PAULETTE; et al. (My University, 2021)
Abstract Background Healthcare workers (HCWs) are at high risk of exposure to SARS-CoV-2. Cross-sectional studies have provided variable rates of seroprevalence in HCWs. Longitudinal assessments of the serological response to Covid-19 among HCWs are crucial to understanding the risk of infection and changes in antibody titers over time. We aimed to investigate seroprevalence and risk factors associated with seroconversion in a prospective cohort of HCWs during the peak of the first wave of the Covid-19 pandemic. Methods We conducted a longitudinal study among 446 front-line HCWsin a tertiary-care hospital in Chile from April to July 2020. IgG was determined monthly using two different ELISAs in serum samples of HCWs, during the three-month period. In each visit, demographic data, symptoms, risk factors, and exposure risks were also assessed. Results The overall seroprevalence at the end of the study period was 24% (95% CI20.2–28.3), with 43% of seropositive HCWs reporting no prior symptoms. Seroconversion rates significantly differed over the study period, from 2.1% to as high as 8.8% at the peak of the epidemic. There were no statistically significant differences observed between HCWs in direct clinical care of patients with Covid-19 and those working in low risk areas. Antibody titers appeared to wane over time. Conclusions HCWs were severely affected with a high rate of seroconversion that appeared to mirror the local epidemiological situation. A significant amount of participants underwent an asymptomatic infection, highlighting the need for improved surveillance policies. Antibody titers appear to wane over time; further studies to understand this finding’s impact on the risk of reinfection are warranted.
Keywords: covid-19; sars-cov-2; seroprevalence; seroconversion; healthcare workers; adult; aged; antibodies, viral; chile; cohort studies; covid-19; covid-19 serological testing; enzyme-linked immunosorbent assay; female; health personnel; humans; immunoglobulin g; longitudinal studies; male; middle aged; prospective studies; sars-cov-2; seroconversion; seroepidemiologic studies; tertiary care centers; immunoglobulin g; sars-cov-2 antibody; immunoglobulin g; virus antibody; adult; aged; antibody titer; article; asymptomatic coronavirus disease 2019; blood sampling; chile; cohort analysis; controlled study; coronavirus disease 2019; demography; disease surveillance; enzyme linked immunosorbent assay; female; health care personnel; high risk population; human; infection risk; longitudinal study; major clinical study; male; occupational exposure; occupational hazard; pandemic; prospective study; reinfection; risk factor; seroconversion; seroprevalence; symptom; tertiary care center; trend study; blood; diagnosis; epidemiology; health care personnel; immunology; middle aged; procedures; seroepidemiology; tertiary care center